2012
DOI: 10.1097/iae.0b013e31824bebb8
|View full text |Cite
|
Sign up to set email alerts
|

Intravitreal Injection of Ranibizumab During Cataract Surgery in Patients With Diabetic Macular Edema

Abstract: In this case series of patients with diabetic macular edema refractory to laser therapy, intravitreal ranibizumab administered during cataract surgery was associated with no significant change in central subfield thickness postoperatively. Significant improvement in best-corrected Early Treatment Diabetic Retinopathy Study visual acuity was observed after treatment, likely because of cataract removal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
19
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 25 publications
2
19
1
Order By: Relevance
“…Although one prospective study found a benefit with BVB treatment with reduced CMT and improved BCVA in comparison to controls at up to three months post operatively, 36 two further prospective studies found that concurrent treatment with BVB or ranibizumab only prevented the worsening of DME post operatively in comparison to controls, with the actual CMT largely remaining unchanged from baseline, indicating that the anti-VEGF treatment failed to reduce the severity of the pre-existing DME post operatively. 19,37 Our pilot data supports these findings, as the CMT in our BVB group tended to increase slightly over the 6 month post-operative period, rather than improve, despite multiple re-treatments.…”
Section: Discussionsupporting
confidence: 71%
“…Although one prospective study found a benefit with BVB treatment with reduced CMT and improved BCVA in comparison to controls at up to three months post operatively, 36 two further prospective studies found that concurrent treatment with BVB or ranibizumab only prevented the worsening of DME post operatively in comparison to controls, with the actual CMT largely remaining unchanged from baseline, indicating that the anti-VEGF treatment failed to reduce the severity of the pre-existing DME post operatively. 19,37 Our pilot data supports these findings, as the CMT in our BVB group tended to increase slightly over the 6 month post-operative period, rather than improve, despite multiple re-treatments.…”
Section: Discussionsupporting
confidence: 71%
“…The only factor found to be associated with visual outcome was the timing of intravitreal injections, with those receiving injections either at the time of surgery or within the 4 weeks preceding surgery being more likely to have a gain in VA, which is consistent with previous reports 8,10,11 . Although the vast majority of patients in this study received anti‐VEGF treatment, there was a slightly higher usage of corticosteroids in the cataract surgery group (8% vs 3%), which may reflect the increased rate of cataract formation from corticosteroid use, or a conscious switch to corticosteroids due to their longer lasting effect on DMO in this setting 11 .…”
supporting
confidence: 86%
“…Although, there have been advances in the treatment of DMO, the most efficacious treatment regime in the perioperative setting is still yet to be determined. Reports of the use of intravitreal anti‐VEGF agents either at the time of surgery or in the weeks preceding surgery generally show it to be an effective treatment in stabilizing or improving central subfoveal thickness (CST) and VA 8‐10 . Similarly, intravitreal corticosteroids have been shown to be effective in this clinical scenario 11,12 .…”
mentioning
confidence: 99%
“…We hypothesize that intravitreal triamcinolone administration may play a positive role in controlling the acute inflammatory factors that are released following cataract removal. The increase in the CST in the group of patients injected intraoperatively with bevacizumab is consistent with the results achieved by Rauen et al (17) , who did not find a positive anatomical response with intraoperative ranibizumab, in contrast to other similar studies (15)(16)(17)(18)(19) . These results may be related to the high percentage of patients (84.7%) previously treated for DME in this group, as it is known that the presence of DME before the cataract removal is a risk factor for developing macular thickening with this surgical procedure.…”
Section: Discussioncontrasting
confidence: 48%
“…Intravitreal anti-VEGF (bevacizumab or ranibizumab) (15)(16)(17)(18)(19)(20) and intravitreal steroids (triamcinolone acetonide or dexamethasone implant) (20)(21)(22) have been reported to achieve positive anatomical and functional results when injected immediately after the surgical procedure. More recently, the efficacy of topical non-steroidal anti-inflammatory drugs has also been reported (23) .…”
Section: Discussionmentioning
confidence: 99%